Inhibition of Parasite Protein Kinase C by New Antileishmanial Imidazolidin-2-one Compounds (2002)
ABSTRACT: The protein kinase C (PKC) family of isoenzymes mediate a wide range of signal transduction pathways in many different cells lines. Little is known regarding the presence and functional roles of PKC in Leishmania spp. Here we report the inhibition of parasite PKC by new imidazolidinone compounds. The most active derivative 7 showed an important activity (IC50 = 9.9 microM) against the clinical relevant stage of parasites in comparison with Glucantime (IC50 = 464.5 microM), without inducing toxicity on human fibroblast cells (IC50 = 102 microM). Pretreatment of intact parasites with 10 microM of compound 7 inhibited 80% of PKC activity. At the same concentration, this compound inhibited 70% of the parasite-host cell invasion process. An in vivo model showed that compound 7 reduced the liver parasite burden by 25% and spleen parasite burden by 44%. These results provide the first evidence that PKC plays a critical role in the invasion process. Thus Leishmania PKC activity could be a relevant therapeutic target and the imidazolidinones novel antileishmanial candidates.